Comparative study of several hypoglycemic sulfamides in alloxanized dogs (Revista Española de Fisiología, 1959)
A comparative study of the hypoglycaemic action of the B-Z-55, D-860 and the N-(4-isopropoxi-benxoly)-p-amino-benzo- sulfanilamide is done on alloxanized dogs.The alloxanized dogs had received 75 to 80 mg of alloxan by rapid endovenous injection, 48 hours before the expe- riments. This time was considered mínimum to attain the cons- tancy of glycaemia.In all the animáis, the sulfanilamide dose has been 200 mg per Kg, orally administrated.The results are given in the figure in per cent. 4 hours after the sulfanilamide dose, a decrease of 5 and 2 % with B-Z-55 and Sulfaproxiline respectively is seen in opposition to a 5 % increase with D-860. 6 hours after a 5 % decrease with B-Z-55 is¡ found and 1 and 5 % increase with D-860 and Sulfa- proxilene respectively. Finally, after 8 hours, the decrease with B-Z-55 is lower than 2 %, the increase with Sulfaproxiline remains at 5 % and with D-860 the increase is smaller than 2 %.It is deduced from this facts that in the experimental condi- tions of time and on alloxanized dogs, the B-Z-55 is the drug possessing the most constant, although light, hypoglycaemic action.